Mobile web to control farming system (MFS) - Muhammad Aidil Azhar, Noor Azmi (2015)
In the present modern agriculture continues to grow by leaps and bounds. Many technologies have been developed agricultural systems in the new millennium era. Accordingly, IT technology (network) is also capable of developing modern agriculture with the use of IT systems. In addition, the IT facilities in agricultural systems can make employees work more comfortable and save energy. Peasant farmers Malaysia now many still use the old method and it causes them to need a lot of manpower to manage their agricultural park perfectly. Can they hire too many workers to keep their farms? So I am planning to build a system using technology IT. This is because mobile phone technology has been used extensively. By using a wireless network, all things can be overcome piping where the pipe system can be controlled to open and close the drain pipe for watering and fertilizing plants. Communication between sensor nodes and servers is achieved through wireless modules. The architecture of the whole system shows the advantages of cost, size, flexibility and power it is believed that the result of the project allows the opportunity to perform research and development.